Mendelian randomization unraveled: gender-specific insights into obesity-related phenotypes and colorectal cancer susceptibility - Chen, Xinyi; Yang, Mu; Zhao, Weiheng; Tu, Jingyao; Liu, Qingxu; Yuan, Xianglin (Frontiers in Endocrinology, 2024)
Abstract Objective: Evidence has been increasingly pointing towards a potential link between phenotypes related to obesity and the incidence of colorectal cancer. However, confirming this as a direct causal connection remains elusive. This investigation aims to elucidate the causative links between obesity-associated phenotypes and the incidence of colorectal cancer. Methods: Employing the Two Sample Mendelian Randomization (TwoSampleMR) R package, analyses were conducted using Mendelian randomization (MR) to discern potential causative links between obesity categories sourced from both the Institute for Education and University (IEU) Open GWAS Project and Zenodo, and colorectal tumors (data obtained from IEU Open GWAS and FinnGen). For primary evaluations, the study utilized the Wald ratio and the Inverse Variance Weighting (IVW) methods, while the MR-Egger approach was integrated for sensitivity assessment. Bidirectional Mendelian Randomization (Bidirectional MR), as well as Linkage Disequilibrium (LD) Score Regression with well-imputed HapMap3 single nucleotide polymorphisms (SNPs), were additionally executed. Sensitivity assessments entailed IVW, MR-Egger methodologies to assess heterogeneity and pleiotropy, along with a leave-one-out strategy. Instrumental variables were chosen judiciously based on predetermined P-value thresholds and F-statistics. Results: Results from MR evaluations did not identify a clear causative link between BMI and colorectal malignancy. Conversely, both measures of obesity, the Waist-Hip Ratio (WHR) and its adjusted form for BMI (WHRadjBMI), displayed a connection to increased risk of colorectal cancer, especially prominent among female subjects. Reverse MR analyses dismissed potential reverse causality between colorectal malignancies and obesity. A significant genetic interplay was observed between WHR, WHRadjBMI, and colorectal cancer instances. Ensuing MR probes spotlighted inflammatory bowel ailment as a protective factor, while salad intake was indicated as a potential risk concerning colorectal malignancies. Sensitivity reviews, which included tests for both pleiotropy and heterogeneity, validated the robustness of the MR findings. Conclusion: Findings from this research indicate that specific obesity-related parameters, notably WHR and WHRadjBMI, carry a causal relationship with an elevated colorectal cancer risk. The impact is distinctly more evident among females. Such insights might be pivotal for public health deliberations, hinting that individuals boasting a high WHR might necessitate intensified colorectal cancer screenings.